Transformational Leadership Creates a Talent Pool Within an Organization: Library Research - Nuraeni Nuraeni; Josua Panatap Soehaditama; Primadi Candra Susanto (Greenation Management and Business Review, 2024)
This article discusses how transformational leadership can create and develop a talent pool in an organization. Through an approach that focuses on inspiration, motivation, and individual development, transformational leaders play a key role in increasing employee engagement and commitment. This research examines various studies and literature that show that transformational leaders not only encourage employees to reach their full potential but also create a work environment that supports innovation and collaboration. By promoting a clear vision, providing individual attention, and encouraging critical thinking, these leaders can identify and develop employee skills and abilities, which in turn strengthens the organization's competitiveness. The research results show that organizations that apply transformational leadership principles have better access to internal talent, which contributes to long-term sustainability and growth. This article concludes that investing in transformational leadership is an effective strategy for building a talent pool that is strong and responsive to changing market dynamics. with a qualitative approach.